2013
DOI: 10.1002/gcc.22047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Targeted Next‐Generation Sequencing (NGS) and Real‐Time PCR in the Detection of EGFR, KRAS, and BRAF Mutations on Formalin‐Fixed, Paraffin‐Embedded Tumor Material of Non‐Small Cell Lung Carcinoma—Superiority of NGS

Abstract: The development of tyrosine kinase inhibitor treatments has made it important to test cancer patients for clinically significant gene mutations that influence the benefit of treatment. Targeted next-generation sequencing (NGS) provides a promising method for diagnostic purposes by enabling the simultaneous detection of multiple mutations in various genes in a single test. The aim of our study was to screen EGFR, KRAS, and BRAF mutations by targeted NGS and commonly used real-time polymerase chain reaction (PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 38 publications
4
111
0
3
Order By: Relevance
“…The statement is evidence based and supported by 5 studies, 169e173 comprising 1 PCS, 172 2 PRCSs, 171,173 and 2 RCSs. 169,170 All included studies were assessed for quality and none were found to have methodologic flaws that would raise concerns about the studies' findings (SDC Table 22).…”
Section: Expert Consensus Opinionmentioning
confidence: 86%
“…The statement is evidence based and supported by 5 studies, 169e173 comprising 1 PCS, 172 2 PRCSs, 171,173 and 2 RCSs. 169,170 All included studies were assessed for quality and none were found to have methodologic flaws that would raise concerns about the studies' findings (SDC Table 22).…”
Section: Expert Consensus Opinionmentioning
confidence: 86%
“…The additional deletion in the EGFR gene was concomitant with the G12D KRAS mutation in one patient, and with a V600E BRAF mutation in another patient. KRAS, BRAF and EGFR mutations are normally exclusive (9) but concomitant KRAS and EGFR mutations have already been described (10,11). The identification of concomitant mutations should increase with the higher sensitivity of NGS technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies showed successful sequencing results in samples with >20% tumor content [3,5,8]. An EGFR mutation was called for in all samples with tumor-cell content >22.8% [3].…”
Section: Page 2 Ofmentioning
confidence: 99%
“…However, demand for improved sensitivity of direct sequencing and resolving the inconvenience of multiple sequential testing practices for real-time PCR has increased [2,3]. Targeted NGS can overcome these limitations of DS or real-time PCR, and showed that NGS tests are accurate and feasible to detect clinically relevant cancer mutations as daily routine diagnostics [4][5][6]. Thus, targeted NGS has been suggested for routine diagnostics and is now widely used in the molecular pathology laboratories [4][5][6].…”
Section: Introductionmentioning
confidence: 99%